The Decision Supporting Factors for Used Car Buying - Suwangsih, Iwang; Setiawan, Ilham Wahyu; Sari, Anita Kartika; Kusmayati, Nindya Kartika; Ali, Umar (Perkumpulan Pendidik Kewirausahaan Indonesia (Perwira Indonesia), 2023)
The aim of this research is to observe and analyze the effect of promotion, price and product quality on the buying decision of used cars in the city of Surabaya. The sample of this research is 97 respondents. Data were processed with SPSS software version 25. The results of the multiple linear regression equation test Y = 6.840 + 0.031X1 + 0.043X2 + 0.613X3, and the t test showed that price had a significant positive effect. This indicated that price was a reinforcing factor for customers to make purchases. used car. The outcomes of the F test is known that all independent variables together have a significant positive influence on the decision to buy a used car. The value of R square (R2) is 0.554.